2011
DOI: 10.1177/1040638711403415
|View full text |Cite
|
Sign up to set email alerts
|

Detection ofCryptosporidiumspecies in feces or gastric contents from snakes and lizards as determined by polymerase chain reaction analysis and partial sequencing of the 18S ribosomal RNA gene

Abstract: Abstract. Cryptosporidiosis is a well-known gastrointestinal disease of snakes and lizards. In the current study, 672 samples (feces and/or gastric contents or regurgitated food items) of various snakes and lizards were examined for the presence of cryptosporidia by polymerase chain reaction (PCR) assay targeting a part of the 18S ribosomal RNA gene. A consecutive sequencing reaction was used to identify the cryptosporidian species present in PCR-positive samples. Cryptosporidium varanii (saurophilum) was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…oocysts, identifying C. varanii (n = 3), C. serpentis (n = 2) and C. parvum (n = 2). A similar study performed in Austria, detected C. varanii and C. serpentis (32/74 and 8/74 leopard geckos, respectively) (Richter et al, 2011). In the present study, molecular identification of Cryptosporidium spp.…”
Section: Resultssupporting
confidence: 48%
See 1 more Smart Citation
“…oocysts, identifying C. varanii (n = 3), C. serpentis (n = 2) and C. parvum (n = 2). A similar study performed in Austria, detected C. varanii and C. serpentis (32/74 and 8/74 leopard geckos, respectively) (Richter et al, 2011). In the present study, molecular identification of Cryptosporidium spp.…”
Section: Resultssupporting
confidence: 48%
“…were detected by Ziehl-Neelsen staining. Previous studies highlight the importance of molecular diagnostic methods to identify species level within the genus Cryptosporidium (Richter et al, 2011). In Spain, Pedraza-Diaz et al (2009) performed PCR and sequencing from seven leopard geckos stool samples with Cryptosporidium spp.…”
Section: Resultsmentioning
confidence: 99%
“…The pooled sample and additional feces from each animal collected 5 days later were examined for Cryptosporidium oocysts with a CST for oocysts, 12 a commercial coproantigen ELISA f (enzyme immunoassay [EIA], previously described 5 and used as a commercially provided kit), and a PCR assay targeting a part of the 18S ribosomal RNA (rRNA) gene. 18 Four samples were positive with the CST, 5 samples were positive and 1 had a threshold value with the EIA, and 6 samples were positive and 2 had threshold values with the PCR (Table 1). The 2 initially presented tortoises with symptoms consistent with cryptosporidiosis (505110, 510210) tested positive with the EIA and PCR or only with the PCR.…”
mentioning
confidence: 99%
“…Cryptosporidium varanii has also been described in ophidian species, and a recent study found a 16% prevalence of C. varanii in fecal samples from corn snakes (Pantherophis guttatus). 18 Clinical signs have mainly been described for lizards and include emaciation, anorexia, and regurgitation. 4 14 An Italian study found 7 of 21 captive Testudo spp.…”
mentioning
confidence: 99%
See 1 more Smart Citation